Case Report: Dural infiltration of intervertebral disc material mimicking spinal cord meningioma in a dog - Sakamoto, Karin; Nakano, Yukiko; Chambers, James K.; Kobatake, Yui; Mizuno, Masao; Kamishina, Hiroaki (Frontiers in Veterinary Science, 2025)
A six-year-old mixed-breed dog presented with a two-month history of peracute back pain and right hindlimb monoparesis. Neurological examination revealed reduced proprioceptive positioning of the right hindlimb, and palpation of the L2–L4 area elicited a pain response. Magnetic resonance imaging revealed a contrast-enhanced mass extending to the dura mater, located on the right ventral side of the spinal cord at the level of the L2–L3 vertebral bodies. A hemilaminectomy was performed to remove the mass. Histopathological examination revealed that the removed dura mater comprised intervertebral disc material that had infiltrated the dura mater. Postoperatively, the dog experienced temporary right hindlimb lameness, which resolved within 24 h. At three years and five months postoperatively, the dog was ambulatory without any neurological deficits or pain. This is the first report of dural infiltration of intervertebral disc material mimicking a spinal cord meningioma in a dog.